FACTORS AFFECTING THE AMOUNT OF SMALL AND MEDIUM ENTERPRISES (SMEs) LOANS OF COMMERCIAL BANKS IN THAILAND - Srirajan, Korakot; Pongsupatt, Apichat (Journal of Buddhist Education and Research (JBER), 2023)
The purpose of this study was to explore factors affecting the amount of small and medium enterprises (SMEs) loan of commercial banks in Thailand. In this study the secondary data were collected from first quarter of 2005 to the 4th quarter of 2021 in total 68 quarters. This study examined six independent variables including Minimum Loan Rate (MLR), unemployment rate (UNE), non-performing loan to loans (NPL), capital adequacy ratio (CAR), liquidity coverage ratio (LCR) and private investment index. This data was analyzed by qualitative and quantitative data analysis using the Ordinary Least Square Method model. The results showed that factors affecting the amount of small and medium enterprises (SMEs) loan of commercial banks in Thailand with statistical significance level of 0.05 in the positive was Minimum Loan Rate (MLR). Meanwhile, unemployment rate (UNE) and non-performing loan to loans (NPL) were negative correlation to loan amount of small and medium enterprises (SMEs) with an R-Square of 0.3408.